Nutraceutical effect of minerals on performance, immunity, and antioxidant system of suckling piglets - Gebert R.R.* (2019)
© 2019, Springer-Verlag London Ltd., part of Springer Nature.The aim of this study was to evaluate whether the use of a mineral complex improves the performance and health of suckling piglets in the maternity phase. Three groups were formatted as follows: control group T1, administration of parenteral minerals on day of birth T2 (0.1 mL of piglet), and 3 days after birth T3 (0.1 mL of piglet). The body weight and blood samples were analyzed at birth and at days 7, 14, and 21 of age. No significant difference in weight gain (p > 0.05). Plasma superoxide dismutase and glutathione peroxidase activities, as well as the antioxidant capacity against peroxyl radical levels, were superior (p < 0.05) in the groups T2 and T3 compared to T1 at specific time points during the experiment, while the lipid peroxidation levels were lower in these groups compared to T1 on day 7 of experiment (p < 0.05). Moreover, an increase on plasma globulins and a decrease on plasma triglyceride levels were observed in animals from group T3 compared to T1 on day 21 (p < 0.05). Animals from groups T2 and T3 presented a higher number of erythrocytes and hemoglobin content compared to group T1 on day 21, as well as observed for total leukocyte count (p < 0.05). The results suggest a nutraceutical effect of minerals in the stimulation of erythropoiesis, immune response, and antioxidants.